Determination of Fetal Maturity Using Signal Transformations of Fetal Thalamus Estimating Fetal Maturity by Ultrasound - Dzikova, Elena; Dimitrov, Goran; Stojceva-Taneva, Olivera; Dimitrov, Gligor (Walter de Gruyter GmbH / Macedonian Medical Association, 2017)
Abstract Introduction. The complications associated with preterm birth are still the primary cause of death in children below 5 years of age, leading to nearly 1 million death cases in 2013. We performed our study to examine a new non-invasive method for prediction of fetal maturity. Methods. The study was designed asa prospective observational-interventional clinical study, conducted at the University Clinic for Gynecology and Obstetrics, Medical Faculty, University Ss. Cyril and Methodius Skopje, Republic of Macedonia. Ninety pregnant patients were examined, 48 with preterm birth used as examined cases and 42 women above 37 completed weeks of gestation and delivered at term, used as control cases. The investigation was performed before and 72 hours after administration of the therapy protocol for fetal lung maturation. The measurement was done with an ultrasound histogram software, measuring the density of thalamus and surrounding brain tissue. The results were followed up to 72 hours and then compared with the postpartum respiratory distress syndrome (RDS). If the patient was not delivered within 72 hours of measurement, she was excluded from the study. Results. In the first and in the second gestational age group, we noticed significant fetal maturation. All groups according to nationality and religionshowed high significance before and after treatment. The correlation among the thalamus density vs. surrounding brain tissue and postpartum RDS in all three groups according to gestational age, nationality and religion was high. Conclusion. Measuring the density of fetal thalamus vs. surrounding brain tissue may become the new non-invasive technique for determination of fetal maturity.